EVALUACIÓN DE LA COMBINACIÓN DEL METHOPRENE 15% YPERMETRINA 65% PARA EL CONTROL DE PULGAS Y GARRAPATAS EN CANINOS - Vega P., Yesenia (2012)
Two field tests were conducted to evaluate the effectiveness and the residual effect oftheMethoprene 15%- Permetrina65%combination and the Imidacloprid6%- Permetrina 24% combination applied as spot on in the control of fleas and ticks in canine, under natural infestation during July and October 2004. In the first assay for flea control were used 30 dogs froma poultry farm located at the Huertos deManchay, Lima, distributed in 3 groups: a) control untreated, b) treatedwith Imidacloprid 6%- Permetrina 24%at a dose of 1 ml/10 kg bodyweight, and c) treated with Methoprene 15% - Permetrina 65% at a dose of 2 ml for animals less than 15 kg and 3ml for animals with more than 15 kg of body weight. In the second assay for tick control were used 16 dogs of the Pachacamac district of Lima, distributed in two groups: a) treatedwith Imidacloprid 6%- Permetrina 24%, and b) treated with Methoprene 15% - Permetrina 65% at the doses used in the first assay. Both combinations of drugs for the flea control showed an effectiveness higher than 90%at 2 weeks after treatment and a residual effect for 21 and 14 days after treatment for the first and second combination respectively. Likewise, both combinations for the tick control showed an effectiveness higher than 90% at 4 weeks after treatment and the residual effect lasted during the 4 week evaluation period.